Analysis of the guiding rules of the nurse technician's practice in Brazil - Marília Souto de Araújo; Soraya Maria de Medeiros; Edilma de Oliveira Costa; Jonas Sâmi Albuquerque de Oliveira; Raphael Raniere de Oliveira Costa; Yanna Gomes de Sousa
ABSTRACT Objectives: to analyze the normative bases that guide the nurse technician's practice, clarifying how the performance of this category happens. Methods: this is a qualitative study of exploratory and descriptive nature and of documentary type, held on the basis of the resolutions of the Brazilian Federal Nursing Council (Cofen). From a total of 364 resolutions published from 1975 to 2018, 15 accounted for the objective of the study and were therefore selected. Results: this study systematized two analytical categories: areas of practice of the nurse technician, according to Cofen resolutions; and description of the professional's activities based on the resolutions. Final Considerations: the analysis of the normative bases that guide the nurse technician's practice leads to the conclusion of a possible frailty of theoretical and normative content to justify the practice of these professionals.